Medical knowledge in Brazil about palliative care: Integrative systematic review (Research, Society and Development, 2023)
This study aims to show medical knowledge about palliative care in Brazil. Palliative care (PC) is a term used to designate a set of actions employed by a highly skilled multidisciplinary team in order to alleviate the suffering of patients and families facing terminal illnesses. This is bibliographical research, of the integrative review type, through a search in the databases: SCIELO, MEDLINE and LILACS. The present study used the following descriptors: “Palliative care”, “Medical education”, “Patient care” in association with Boolean operators AND and OR. Data collection was carried out following six methodological steps: The first step was related to the proposed objectives. The second step was to determine the inclusion or exclusion criteria for articles. The third stage was collecting information from the selected studies and stratifying them. The fourth stage was the evaluation of the methods used in the studies. The fifth stage was the interpretation and discussion of the results, and the last stage was the presentation, argumentation and conclusion. 150 articles were identified, of which only 100 met the eligibility criteria, however, 85 of them did not meet the project regulations. Thus, 5 articles were selected that relate medical knowledge about palliative care. The discussion was conducted on the results, respecting comparative criteria between objective, thematic associations and conclusion. In conclusion, it appears that the inclusion of CP teaching in undergraduate courses is deficient in Brazil, and all studies reveal the need to address the topic to improve students’ comprehensive vision.